Standard Terms on the TikTok Digital Platform Regarding the Revocation of Live Streaming Access Under the Consumer Protection Act - Rendika Purnama; Suherman Suherman (NOTARIIL Jurnal Kenotariatan, 2026)
This study aims to analyze the standard clauses in TikTok’s Terms of Service and the platform’s liability regarding the restriction of live streaming access during the events of August 31, 2025, from the perspective of consumer protection law in Indonesia. This study employs a normative legal method using a statutory approach and a case-based approach, and is analyzed descriptively and qualitatively based on primary and secondary legal sources. The results of the study indicate that the standard clauses in TikTok’s Terms of Service tend to grant unilateral authority to the platform, particularly regarding service restrictions and limitations of liability. These clauses potentially conflict with the Consumer Protection Law, the principle of good faith under the Civil Code, and the obligations of electronic system operators to ensure service reliability. The incident of live streaming termination without adequate notice highlights a gap between applicable legal provisions and on-the-ground practices. The study’s conclusion reaffirms that digital platforms retain legal liability for policies that harm users, and standard clauses cannot be used to evade such obligations. This research is expected to strengthen consumer protection within the digital ecosystem.